"Spare Wheel" R&D in vertically related markets. (23rd August 2021) - Xue, Mantian
Abstract : In vertically related markets, downstream firms might launch Spare Wheel R&D plans to deal with potential embargoes enforced by countries where upstream monopolies are located. The existence of Spare Wheel R&D requires several conditions to be satisfied, including the equivalence of the upstream country's expected social welfare of different strategies, higher social welfare of the upstream country when choosing to export, moderate R&D efficiency, and relatively low R&D cost of the downstream firm. Besides, the most appropriate strategic R&D policy of the downstream country is to support the downstream firm's R&D project after the embargo is imposed.